Exploring microbial signatures in sarcoidosis: etiological and therapeutic implications of host–microbiota interactions - Rizzi, Luigi; Larizza, Giovanni; Suppressa, Patrizia (Frontiers in Immunology, 2026)
Sarcoidosis is a chronic inflammatory disease that can potentially affect any organ. From a pathogenetic standpoint, it is characterized by the formation of chronic granulomatous inflammation, which defines its histological hallmark. Unlike its pathogenetic mechanisms, the etiology of sarcoidosis remains poorly understood. Environmental triggers—such as viruses, bacteria, fungi, or exposure to damp environments—have been hypothesized as risk factors in genetically predisposed individuals. Recently, increasing attention has been given to the role of the gut microbiota in the development of various metabolic and autoimmune disorders. At this regard, the primary aim of this review has been to critically explore the potential role of the gut and lung microbiota in the onset of sarcoidosis. We examined current and available evidence regarding the composition of the pulmonary and intestinal microbiota in sarcoidosis, identifying possible differences compared to other interstitial lung diseases and trying to find potential correlations with the etiological and prognostic features of the disease. Furthermore, potential therapeutic implications for the treatment of sarcoidosis have been assessed, with a focus on the possibility of modulating the microbiota of affected individuals as a novel approach.